ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM CHICKEN KATSU KARAWANG DENGAN METODE FULL COSTING - Itanova, Hani; Ramadhina, Flora Oktayovie Nuzulul; Maula, Kholida Atiyatul (Politeknik Negeri Semarang, 2024)
The calculation of the cost of goods produced is very important for all businesses. However, there are still many entrepreneurs who do not calculate in detail the cost of goods sold. This can cause misinterpretation of the assumption of profit or loss of a business. This research focuses on calculating the cost of goods produced in one of the Chicken Katsu Karawang MSMEs. With the calculation and comparison of the calculation of COGS of the full costing method and the estimated COGS of the business, it is hoped that it can help determine the appropriate product selling price. This research uses interviews, observations, and literature. With the full costing method, the result of the COGS calculation is Rp652, - higher per product. So that there are differences in profit assumptions. Therefore, Chicken Katsu MSMEs are advised to calculate all raw material costs, variable overhead costs and fixed costs in detail and apply the full costing method as a business calculation method in order to determine the actual cost of goods sold.